Bronchopulmonary dysplasia—A historical perspective. Issue 11 (13th March 2021) - Allen, Julian; Panitch, Howard
Abstract: Bronchopulmonary dysplasia (BPD) was first described by Northway et al in 1967. This article describes the evolution of our understanding of the pathophysiology of BPD and the approaches to treatments of this illness developed over the past fifty years. These interventions had their roots in the understanding of the principles of the surface tension present at air–liquid interfaces, which were developed over 150 years before BPD's initial description. Improving outcomes in neonatal care have led to greater survival of preterm and very preterm infants, and to an evolution of the pathogenesis and pathology of BPD, from an illness caused primarily by barotrauma and oxygen toxicity to one of interruption of lung development. While the incidence of BPD has remained about the same in recent decades, this is because survival of infants born at lower gestational ages is increasing. Understanding of molecular, genetic and physiologic mechanisms has led to newer treatments that have mitigated some of the harmful effects of prolonged mechanical ventilation. Recognition of BPD as a chronic multi‐system disease has resulted in further improvements in care after discharge from neonatal intensive care. Since many of the origins of chronic obstructive lung disease in adults are based in childhood respiratory illnesses, improving outcomes of BPD in infancy and childhood will undoubtedly lead to improved respiratory outcomes in the adults that these children will become.